Physico-mechanical properties of polymer concrete containing micro-filler of palm oil fuel ash - A. Khalid, Nur Hafizah; Ismail, Mohammad; Mohd. Sam, Abd Rahman; Mohamed, Azman; A. Ismail, Mohamed; Jamellodin, Zalipah; Salleh, Norhafizah; A. Hamid, Noor Azlina; A. Majid, Masni (American Scientific Publishers, 2018)
Objective of this study is to present a research conducted on ground (fine) and unground (coarse) POFA in polymer concrete (PC) followed by determination on the physico-mechanical properties of PC. Physical properties of micro-fillers and mechanical properties of produced PCs were characterized. Calcium carbonate and silica sand were also used as micro-fillers for comparison purpose. The samples were subjected to compression and flexural. Morphology images of the particles were captured under morphology test to support the findings. Results showed that fine POFA micro-filler has a highly promising potential in becoming PC filler compared to coarse micro-filler. Additionally, its produced PC had comparable strength to PC with calcium carbonate. From the strength development and sustainability stand point, fine POFA has demonstrated its capability to produce quality and sustainable PC